Time response of rat testicular alterations induced by cryptorchidism and orchiopexy - Ferragut Cardoso, Ana P. [UNESP]; Gomide, Lígia M. M. [UNESP]; Souza, Nathalia P. [UNESP]; de Jesus, Carlos Márcio N. [UNESP]; Arnold, Lora L.; Cohen, Samuel M.; de Camargo, João Lauro V. [UNESP]; Nascimento e Pontes, Merielen G. [UNESP] (Wiley, 2021)
Cryptorchidism is one of the main risk factors for infertility and testicular cancer. Orchiopexy surgery corrects cryptorchidism effects. Different models of cryptorchidism developed in the rat include surgery. We assessed testicular alterations in rats submitted to surgical cryptorchidism and examined their potential for reversibility at different time points in order to verify time dependency effect(s) on the recovery of the undescended testes. Cryptorchidism was induced in 3-week-old rats. Animals were euthanized 3, 6 or 11 weeks after surgery to evaluate the morphological progression of cryptorchidism-induced germinative epithelial alterations. Other groups underwent orchiopexy 3, 5 or 9 weeks after surgical cryptorchidism, before or after puberty. Animals were euthanized 3 or 8 weeks after orchiopexy. Controls underwent sham surgery at the same time points as the surgical groups. Cryptorchid testes showed decreased weight, germinative epithelial degeneration, apoptosis and vacuolation, corresponding to impairment of spermatogenesis and of Sertoli cells. Some tubules has a Sertoli cell-only pattern and atrophy. The intensity of damage was related to the duration of cryptorchidism. After orchiopexy, spermatogenesis completely recovered only when testicular relocation occurred before puberty and the interval for recovery was extended. These results indicate that age, sexual maturity and extension of germ cell damage were relevant for producing germ cell restoration and normal spermatogenesis. We provide original observations on the time dependency of testicular alterations induced by cryptorchidism and their restoration using morphologic, morphometric and immunohistochemical approaches. It may be useful to study germ cell impairment, progression and recovery in different experimental settings, including exposure to exogenous chemicals.
Keywords: cryptorchidism; germ cell damage; orchiopexy; testicular damage